Information Technology for Management Federated Conference on Computer Science and Information Systems, ISM 2015 and AITM 2015, Lodz, Poland, September 2015, Revised Selected Papers - Ziemba, Ewa (Lecture Notes in Business Information Processing, 2016)
This book constitutes revised and extended versions of the best papers from the 10th Conference on Information Systems Management (ISM 2015) and 13th Conference on Advanced Information Technologies for Management (AITM 2015), held in Lodz, Poland, September 2015 as part of the Federated Conference on Computer Science and Information Systems (FedCSIS 2015). These events constitute a forum for the exchange of ideas for practitioners and theorists working in the broad area of information systems management in organizations and to present and discuss the current issues of IT in business applications. The 11 full papers included in this volume were carefully reviewed and selected originally 54 submissions. They focus on knowledge management systems; information technology for business and public organizations; and evaluation of information systems.